KEARAH INTEGRASI SAINS DAN AGAMA SEBUAH TANTANGAN KONTEMPORER - Wahyu, Wahyu (Institut Agama Islam Negeri (IAIN) Palu, 2007)
One of the salient features of the contemporary world is a rapid change in all aspects of life. This reality, whether we like or dislike, has become a choice leading the Islamic world to awareness that a structural adaptation to this is necessary. Although such an adaptation is a weak form of self-defense, it is an alternative urgently needed to integrate science and religion in order that they do not lose their context and empirical meanings.Kata Kunci : Sains, agama,Â tantangan kontemporer